Implementasi Penggunaan Autonomous Mobile Robot dalam Mendukung Efektivitas Distribusi Logistik: Studi Pada Kantor Sentral Pengolahan Pos Surabaya - Syafira Widya Uni Putri; Nurhadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of technology in the industrial revolution 4.0 era has brought about major changes in the logistics distribution system. Technologies such as Artificial Intelligence (AI), Internet of Things (IoT), and robotic automation have become an important part in improving the efficiency, speed, and accuracy of goods distribution. One implementation that is often used by logistics companies is autonomous mobile robot (AMR). This research was conducted to examine the implementation of AMR use in the logistics sorting process, identify the driving and inhibiting factors, and assess the effectiveness of logistics distribution on operational efficiency, customer satisfaction, and HR efficiency at the Surabaya Postal Processing Center (SPP) Office, which is the logistics sorting branch office of PT Pos Indonesia. By using descriptive qualitative methods, data collection techniques through in-depth interviews, field observations, and operational documentation The results show that the use of robotic technology is able to provide time and cost efficiency, but also poses challenges such as limited human resource adaptation, and the need for high initial investment is an obstacle to the application of robotics. Therefore, the application of this technology needs to be balanced with an inclusive change management strategy in order to have a sustainable positive impact on the company.